El Excentrico, 1975-02-05 - Garcia, Bert:::Publisher::::::::::::; Garcia, Marc:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 5, 1975. [5 de febrero de 1975]. No volume or issue number. Cover has a drawing of a firefighter as an advertisement for Bombero Dance, a social event for firefighters held at the Santa Clara County Fairgrounds.